Bio-based barium alginate film: Preparation, flame retardancy and thermal degradation behavior. (30th March 2016) - Liu, Yun; Zhang, Chuan-Jie; Zhao, Jin-Chao; Guo, Yi; Zhu, Ping; Wang, De-Yi
Highlights: The addition of barium ion obviously improved the flame retardancy of alginate. The addition of barium ion changed the thermal degradation behaviors of alginate. Pyrolysis process of barium alginate produced much less gaseous compounds. Possible thermal degradation mechanism of barium alginate was proposed according to the results of TG-FTIR and Py-GC–MS. Abstract: A bio-based barium alginate film was prepared via a facile ionic exchange and casting approach. Its flammability, thermal degradation and pyrolysis behaviors, thermal degradation mechanism were studied systemically by limiting oxygen index (LOI), vertical burning (UL-94), microscale combustion calorimetry (MCC), thermogravimetric analysis (TGA) coupled with Fourier transform infrared analysis (FTIR) and pyrolysis-gas chromatography–mass spectrometry (Py-GC–MS). It showed that barium alginate film had much higher LOI value (52.0%) than that of sodium alginate film (24.5%). Moreover, barium alginate film passed the UL-94 V-0 rating, while the sodium alginate film showed no classification. Importantly, peak of heat release rate (PHRR) of barium alginate film in MCC test was much lower than that of sodium alginate film, suggested that introduction of barium ion into alginate film significantly decreased release of combustible gases. TG-FTIR and Py-GC–MS results indicated that barium alginate produced much less flammable products than that of sodium alginate in whole thermal degradation procedure. Finally, a possible degradation mechanism of barium alginate had been proposed.